2022
DOI: 10.3390/rs14143462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Snowpack on the Land Surface Phenology in the Tianshan Mountains, Central Asia

Abstract: The accumulation and ablation processes of seasonal snow significantly affect the land surface phenology in a mountainous ecosystem. However, the ability of snow to regulate the alpine land surface phenology in the arid regions is not well described in the context of climate change. The impact of snowpack changes on land surface phenology and its driving factors were investigated in the Tianshan Mountains using the land surface phenology metrics derived from satellited products and a snow dataset from downscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…These findings are consistent with previous model simulations 30 and in situ measurements. 46 The spectral slope of high-level MD snow first shows a significant decrease at 600 nm, making it possible to identify MD-loaded snow using simple mathematical methods such as spectral derivative or change point detection. The impact of ash on snow spectra is more pronounced than that of MD, with its first spectral slope significant decrease point near 700 nm (Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous model simulations 30 and in situ measurements. 46 The spectral slope of high-level MD snow first shows a significant decrease at 600 nm, making it possible to identify MD-loaded snow using simple mathematical methods such as spectral derivative or change point detection. The impact of ash on snow spectra is more pronounced than that of MD, with its first spectral slope significant decrease point near 700 nm (Figure 7A).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the studies included in this Special Issue explore the interrelationships between vegetation and snow cover in the context of climate change and intensive human activity. Yang et al [14] investigated the impact of snowpack changes on land surface phenology and its driving factors in the Tianshan Mountains from 1983 to 2015. Snow and vegetation phenology metrics were derived from satellite products and regional climate model simulations.…”
Section: Overview Of Contribution and Future Perspectivesmentioning
confidence: 99%
“…For example, over the Tibetan Plateau, a series of research based on satellite data found an advancing trend in spring phenology from 1982 to the mid-1990s, but the advance slowed down after the mid-1990s ( Yu et al., 2010 ; Chen et al., 2011 ; Piao et al., 2011 ; Shen, 2011 ; Shen et al., 2011 ). While a continued advance in spring phenology in the first decades of this century, was found in the western Tianshan Mountains, Ili Valley ( Yang et al., 2022 ), and the northern Alps of European ( Meng et al., 2021 ). What’s more, a significant slowing down of spring phenology during 2000-2011 were found in the lowland of the Pan-Third Pole ( Fu et al., 2014 ), with even slight delaying trends detected in the south-western Tibetan Plateau ( Shen et al., 2022 ) and high altitude (>2500 m) of Tianshan Mountains in central Asia ( Ding et al., 2022 ), and French Alps ( Asse et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%